The Application of Profit Sharing of Shirkah Contract During New Normal Era at Micro, Small, and Medium Enterprise (MSME), Warung Sate Joenedin Samarinda - Nurul Fadhilah (JES (Jurnal Ekonomi Syariah), 2022)
This research aims at answering some research questions: How was the shirkah system and the implementation of profit sharing in the new normal era, as well as the benefits and obstacles of implementing the shirkah contract at Warung Sate Joenedin. The research method used is qualitative descriptive analysis approach. Data collection is conducted through observation, documentation, and a direct interview with informants, namely Warung Sate Joenedin partners. The results reveal that the collaboration between the partners of Warung Sate Joenedin is in the form of shirkah inan. Based on the research results, it can be concluded that the cooperation carried out by Warung Sate Joenedin follows the term cooperation from sharia economics perspective. The implementation of profit sharing is based on an agreement, while losses are borned by each partner based on the capital stock. This shirkah cooperation is beneficial for partners, while Warung Sate Joenedin has not experienced losses. In line with the conclusion based on the Islamic economics perspective, the researchers suggested that the cooperation between Warung Sate Joenedin companies should be sustainable.